IMPLEMENTATION OF THE LAW ON THE STATE LANGUAGE: PROBLEMS, OPPORTUNITIES AND SOLUTIONS (Web of Teachers: Inderscience Research, 2024)
This article focuses on the analysis of the implementation of the Law on the State Language of the Republic of Uzbekistan. The law was adopted in 1989 and is aimed at strengthening the position of the Uzbek language as the state language. However, there are a number of problems with its full implementation. This article analyzes the main problems, in particular, the insufficient use of the Uzbek language in scientific and technical fields, public administration and the education system, the underdevelopment of language culture, as well as low public attention to the language. The article also presents solutions necessary for the effective implementation of language policy.